UMPSA and the Pahang State Health Department organized the World Suicide Prevention Awareness Day Symposium and the Pahang State Level Mental Health Day Celebration 2024 - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 19 September 2024 – Recently, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), in collaboration with the Pahang State Health Department (JKNP), organized the World Suicide Prevention Awareness Day Symposium and Pahang State Level Mental Health Day Celebration 2024.